Muslim-Christian Dialogue in the Modern World: Insights and Lessons from Said Nursi’s Legacy - Sohail Ashraf Mir (Al-Abqori: Journal of Islamic Thought Studies, 2026)
Interfaith dialogue is a process of communication and exchange between individuals or groups representing different religions or spiritual traditions. Interfaith dialogue aims to foster understanding and build relationships between people of different faiths, promoting peaceful coexistence and mutual respect. There are and were numerous academicians from the intellectual history of Muslims who have contributed to this field. One such example is Bediuzzaman Said Nursi (1878-1960), a prominent Turkish scholar and theologian on interfaith dialogue. Nursi’s thoughts on interfaith dialogue are rooted in his deep commitment to peaceful co-existence and mutual respect among people of different faiths. Nursi believed that interfaith dialogue is essential in promoting understanding and cooperation between different religions, and it can help to build bridges between communities that have historically been divided. Against this backdrop, this paper examines his ideas on the importance of dialogue, the role of religion in fostering understanding, and the potential benefits of interfaith dialogue for both individuals and societies. Drawing on Nursi’s ideas, this research paper concludes that Muslim-Christian dialogue can benefit from a renewed emphasis on the shared values and principles that underlie both traditions, such as the importance of social justice, compassion, and ethical behaviour.